Effect of Mineral Admixtures on Pervious Concrete. (2018) - Ramkrishnan, R; Abilash, B; Trivedi, Mansi; Varsha, P; Varun, P; Vishanth, S
Abstract: The major problem encountered with impervious pavements is the drainage of surface runoff which deteriorates the wearing course and causes urban heat island effect. Usage of pervious concrete can reduce this effect. Pervious concrete has applications in parking lots, footpaths and can be used in conjuncture with geo-synthetics to prevent beach erosion. The performance of pervious concrete depends on pore structure, cement matrix, aggregate gradation, cement content, admixtures and water/cement ratio. This study on pervious concrete deals with (i) optimal design for high compressive strength and permeability, (ii) durability tests, and (iii) effect of mineral admixtures on strength and durability.